Cornel iridoid glycoside ameliorates cognitive deficits in APP/PS1/tau triple transgenic mice by attenuating amyloid-beta, tau hyperphosphorylation and neurotrophic dysfunction - Yang, Cuicui (Ann Transl Med, 2020)
BACKGROUND: Targeted proteinopathy is involved in creating pharmacological agents that protect against Alzheimer disease (AD). Cornel iridoid glycoside (CIG) is an effective component derived from Cornus officinalis. The present study aimed to determine the effects of CIG on β-amyloid (Aβ) and tau pathology and the underlying mechanisms in APP/PS1/tau triple transgenic (3×Tg) model mice. METHODS: We intragastrically administered 16-month-old 3×Tg mice with CIG (100 and 200 mg/kg) daily for two months. Learning and memory abilities were determined using the Morris water maze (MWM) and object recognition tests (ORT). Amyloid plaques and Aβ40/42 and the expression of related proteins in the cerebral cortex and hippocampus of mice was determined by western blotting RESULTS: CIG improved learning and memory impairment in 3×Tg model mice, decreased amyloid plaque deposition, Aβ40/42 and the expression of full-length amyloid precursor protein, and increased levels of ADAM-10 (α-secretase), neprilysin (NEP), and insulin degrading enzyme (IDE) in the brains of the model mice. CIG also reduced tau hyperphosphorylation, and elevated phosphorylation level of GSK-3β at Ser9 and methylation of PP2A catalytic subunit C in the model mice. Moreover, CIG increased the expression of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and phosphorylated cAMP-responsive element binding protein (p-CREB) in the brain of 3×Tg mice. CONCLUSIONS: CIG ameliorated learning and memory deficit via reducing Aβ content and, tau hyperphosphorylation and increasing neurotrophic factors in the brain of 3×Tg mice. These results suggest that CIG may be beneficial for AD therapy.